Competitive reverse transcriptase-polymerase chain reaction shows that dietary zinc supplementation in humans increases monocyte metallothionein mRNA levels - Sullivan, V K; Cousins, R J (The Journal of nutrition, 1997)
Zinc status is difficult to evaluate in humans. Metallothionein gene expression is transcriptionally regulated by dietary zinc and thus could serve as an assessment parameter based on zinc-dependent function. We used semiquantitative reverse transcriptase-polymerase chain reaction (RT-PCR) to establish that MT mRNA is increased in a human monocytic cell line by addition of zinc to the medium. To examine this response in human subjects, a dietary supplement of 50 mg zinc gluconate/d was given for 15 d. Monocytes were purified from venous blood using NycoPrep 1.068. Monocyte purity was determined by flow cytometry using fluorescent anti-human monocyte CD14 antibodies. Total monocyte RNA was extracted and converted to cDNA by reverse transcription. Competitive RT-PCR was used to analyze differences between cDNA levels that are proportional to MT mRNA levels in monocytes from zinc-supplemented and control subjects. RT-PCR oligonucleotide primers were designed to amplify both a 201 bp segment of the human MT cDNA and a 180 bp competitor cDNA template. The 180 bp competitor cDNA template was used for MT cDNA quantitation. The RT-PCR data show that there was a significant increase in monocyte MT mRNA in subjects within 6 d of zinc supplementation, which remained elevated at d 15 of supplementation. In contrast, plasma zinc was greater at d 6 of zinc supplementation, but by d 15 of supplementation, while still elevated, was close to control levels. These data suggest that monocyte MT mRNA levels respond to zinc supplementation and that the response could serve as a more useful assessment variable than plasma zinc for the measurement of zinc status in humans.